Comparative study of radioactive cesium transfer from soil to peanut and soybean. Issue 6 (2nd November 2021) - Kubo, Katashi; Maruyama, Hayato; Fujimoto, Hisae; Suzuki, Masataka; Kan, Ayane; Unno, Yusuke; Shinano, Takuro
ABSTRACT: Low transfer of radioactive cesium (radiocesium) from soil to grains of agricultural crops is desirable to ensure food safety for humans and animals. Although the transfer of radiocesium from soil to grains is higher in upland crops such as soybean ( Glycine max L.) than in paddy rice ( Oryza sativa L.), little information related to the specific difference in radiocesium accumulation among leguminous crops is available, or for the relation between soil conditions and radiocesium accumulation in leguminous crops. This study compared the pattern of radiocesium transfer from soil to grains between peanut ( Arachis hypogaea L.) and soybean to elucidate the diversity of radiocesium accumulation in leguminous crops growing with different potassium levels in soil. Pot and field experiments with radiocesium-contaminated soil showed that the radiocesium concentration in grains was lower in peanut than in soybean plants. For peanut, radiocesium absorption was mainly from roots instead of gynophores and fruits formed in the soil. Radiocesium absorption and translocation from roots to shoots were lower in peanut than in soybean plants. Among shoot parts, radiocesium transfers from stems to leaves, shells, and grains were lower in peanut than in soybean plants. Potassium application to the soil decreased the radiocesium transfer from soil to grains in both crops. The radiocesium accumulation was lower in peanut than in soybean under both potassium applied and non-applied conditions. These results underscored the variation in radiocesium transfer from soil to grains in leguminous crops, and demonstrated that peanut plants had lower potential of radiocesium accumulation than soybean plants.